2006
DOI: 10.1039/b506061c
|View full text |Cite
|
Sign up to set email alerts
|

Generation of ROS in cells on exposure to CW and pulsed near-infrared laser tweezers

Abstract: We report the results of a study on generation of reactive oxygen species (ROS) and changes in the membrane potential of mitochondria of carcinoma of cervix (HeLa) and Chinese hamster ovary (CHO) cells following exposure to continuous wave (cw) or pulsed Nd: YAG laser (1064 nm). For a given laser irradiation, the generation of ROS and induced changes in the membrane potential of mitochondria were more pronounced for HeLa cells as compared to CHO cells. However, in both the cells the laser dose required to elic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 20 publications
0
28
0
Order By: Relevance
“…Many different laser types have been employed to directly pump monomol and dimol O 2 bands: Nd:YAG and Nd-based [29], [30], [122], [123], [124], [125], [126], [127], [128], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], Yb-based [31], He-Ne [29], [99], [108], [123], [141], [143], [144], [177], [178], [179], [180], [181], semiconductor (diode) [27], [108], [109], [114], [119], [120], [137], [146], [148], [149], [150], [151], [152], [153], [154], [168], Raman-shifted [23], [24], [25], [26], [28], [115], dye-based [174], [185], alexandrite (Cr:BeAl 2 O 4 ) [108], and forsterite (Cr:Mg 2 SiO 4 ) [109] to name the most common ones (more examples can be found in each wavelength subsection above). Visible excitation of O 2 has the drawback of overlapping with endogenous cellular chromophores, like cytochromes, porphyrins, certain cofactors (like flavin- and nicotinamide-containing metabolites), etc [170].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many different laser types have been employed to directly pump monomol and dimol O 2 bands: Nd:YAG and Nd-based [29], [30], [122], [123], [124], [125], [126], [127], [128], [135], [136], [137], [138], [139], [140], [141], [142], [143], [144], Yb-based [31], He-Ne [29], [99], [108], [123], [141], [143], [144], [177], [178], [179], [180], [181], semiconductor (diode) [27], [108], [109], [114], [119], [120], [137], [146], [148], [149], [150], [151], [152], [153], [154], [168], Raman-shifted [23], [24], [25], [26], [28], [115], dye-based [174], [185], alexandrite (Cr:BeAl 2 O 4 ) [108], and forsterite (Cr:Mg 2 SiO 4 ) [109] to name the most common ones (more examples can be found in each wavelength subsection above). Visible excitation of O 2 has the drawback of overlapping with endogenous cellular chromophores, like cytochromes, porphyrins, certain cofactors (like flavin- and nicotinamide-containing metabolites), etc [170].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Nd lasers, mainly Nd-YAG, are widely employed as sources for optical tweezers. However, several publications have reported chemical and biological damage at relatively low light intensities in optical traps at this wavelength [30], [31], [135], [136], [137], [138], [139], [140], [141], [142]. In many of these publications the source of damage has been ascribed to direct thermal action (due to water absorption), organic chromophore excitation in the limit of the absorption band ( e.g .…”
Section: Direct Optical Excitation Of 1o2mentioning
confidence: 99%
“…This is in good agreement with the findings of König et al [23] who concluded that “optical micromanipulation of spermatozoa” with long wavelength nIR laser beam causes significantly less damage as compared to ultraviolet exposure. In contrast, long exposure to the laser trap is reported to have an adverse effect on sperm swimming speed and mitochondrial membrane potential due to laser-induced rise in temperature [24, 25]. Also, depolarization of mitochondria has been observed with prolonged exposure of domestic dog spermatozoa to optical tweezers [25].…”
Section: Discussionmentioning
confidence: 99%
“…Although this spectral range is assumed to be safe and noninvasive to the cells, there are concerns that the laser light, per se, might have damaging effects on the certain types of living specimens, such as DNA damage, loss of membrane potential, cloning efficiency reduction, and loss of viability [2427]. …”
Section: Introductionmentioning
confidence: 99%
“…mal effects [5] are responsible for the adverse effects observed at this wavelength. In this context it is important to note that pre-irradiation with He--Ne laser has been observed to protect wild type E. coli [6,7] against UVC and B-lymphoblast cells against UVA [8] radiation induced damage, which is also believed to be mediated predominantly via ROS generation [9].…”
Section: Biophotonicsmentioning
confidence: 98%